STOCK SPLIT DAN LIKUIDITAS SAHAM DI BEI: PENGUJIAN MENGGUNAKAN HIPOTESIS LIKUIDITAS - Setyawan, Ignatius Roni (UI Scholars Hub, 2010)
This study aims to re-examine the effectiveness of liquidity hypothesis in stock split. Liquidity hypothesis in stock split is defined as the returning stock price to the optimal trading level. Based on Ekaputra and Putri (2006), this study consists of two analysis methods such as: 1) Paired t-test among return volatility and liquidity during stock split 2) OLS-test focuses on the consistency of the model of Ekaputra and Putri (2006) and in line with Kim et al. (2007), this research includes Amihud’s Illiquidity as an alternative proxy of liquidity in stock split in addition to relative spread. According to paired t-test, this study finds return volatility decreases after stock split and it is similar to liquidity proxies both relative spread and Amihud’s Illiquidity. In OLS-test, the results indicate that only the effect of trading volume toward liquidity proxies (i.e., relative spread and Amihud’s Illiquidity) has the appropriate signs with the alternative hypothesis. Generally, this research concludes that stock liquidity increases after stock split and relative spread is a better liquidity proxy than Amihud’s Illiquidity.